2018
DOI: 10.1167/tvst.7.4.14
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Bruch's Membrane Opening-Minimum Rim Width and Retinal Nerve Fiber Layer Thickness and a New Index Using a Neural Network

Abstract: PurposeWe evaluate the relationship between Bruch's membrane opening minimum rim width (BMO-MRW) and peripapillary retinal nerve fiber layer thickness (pRNFLT) and develop a new parameter combining BMO-MRW and pRNFLT using a neural network to maximize their compensatory values.MethodsA total of 402 subjects were divided into two groups: 273 (validation group) and 129 (neural net training) subjects. Linear quadratic and broken-stick regression models were used to explore the relationship between BMO-MRW and pRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 45 publications
2
22
0
1
Order By: Relevance
“…Combining two or more parameters may also further improve the discriminatory ability of the algorithm. 40 In summary, we used the BMO-MRW from SDOCT to train a deep learning algorithm to predict quantitative data about the degree of neuroretinal damage when assessing an optic disc photograph. The predicted quantitative data was correlated with the BMO-MRW value from SDOCT and showed high diagnostic discrimination for glaucomatous visual field loss.…”
Section: Discussionmentioning
confidence: 99%
“…Combining two or more parameters may also further improve the discriminatory ability of the algorithm. 40 In summary, we used the BMO-MRW from SDOCT to train a deep learning algorithm to predict quantitative data about the degree of neuroretinal damage when assessing an optic disc photograph. The predicted quantitative data was correlated with the BMO-MRW value from SDOCT and showed high diagnostic discrimination for glaucomatous visual field loss.…”
Section: Discussionmentioning
confidence: 99%
“…27 In patients without ON history, probably only RNFL and retinal ganglion cell loss due to retrograde axonal degeneration are observed. 3,27 Park et al 16 studied S-RNFL and BMO-MRW techniques in glaucoma. They found that the correlation was most robust in T sectors of advanced glaucoma patients but weak to moderate correlation values in HC subjects.…”
Section: Discussionmentioning
confidence: 99%
“…This situation enables precise examination of the relevant structures and ensures accurate comparisons with reference data, allowing for a highly sensitive assessment of structural change. 12,15,16 In this study, we aimed to investigate the tissue-function (visual functions and disability in MS) relationship in patients with MS by using new parameters of OCT, which are BMO-MRW and RNFL measured using the APS™.…”
Section: Introductionmentioning
confidence: 99%
“…A recent previous study showed that neuroretinal rim thinning of BMO-MRW may precede RNFL thinning through a nonlinear piecewise regression analysis, echoing the findings in several previous clinical and experimental glaucoma model studies. 47 49 Hence, optic nerve parameters may be earlier indicators of glaucomatous damage compared with RNFL thickness.…”
Section: Discussionmentioning
confidence: 99%